The Psychology of a Human Relationship and Its Existence in a Multicultural Society - Boonsit, Pichamon; Chelong, Abdullah (FOYER: The Journal of Humanities, Social Sciences, and Education, 2023)
During public health crises, natural disasters, and social and political crises that are characterized by ambiguity, and uncertainty, it is deeply rooted in people’s systems of thought that insecurity in life can happen at any time. Thus, people have created values and cultures to protect themselves in the face of greater changes, as a catalyst for human beings to adapt to and to seek solutions in a variety of dimensions. This article will give the reader a glimpse of solutions for understanding the psychology of human relationships in a multicultural society through descriptive analysis.